#Cultura digital: reflexiones en torno a los consumos políticos contemporáneos - Taricco, Lucrecia; Paz García, A. Pamela (Pontificia Universidad Católica del Perú. Fondo Editorial, 2020)
In everyday life context, inscribed in the cultural battlefield of the material and symbolic (hyper)mediations of the Internet, we are interested in critically reflecting on the approach to cultural practices of digital consumption. Inside the political communication field, we observe that today multiple phenomena are embedded in the daily configuration of these practices, which lead us to rethink the role of traditional audience measurements and statistics, to the use of big data and algorithms, different political-cultural outlooks of audiences, challenged by a global crisis in the subject of cybersecurity. Among other conditions of going digital, we will thus understand such contemporary consumption as an issue concerning political power, taking into account its ideological dimension.

En el contexto de la vida cotidiana, inscri-ta en el campo de batalla cultural de las (hiper)mediaciones materiales y simbólicas de internet, nos interesa reflexionar críticamente en torno al abordaje de las prácticas culturales de consumo digital. Dentro del campo de la comunicación política, observamos que hoy múltiples fenómenos se imbrican en la configuración cotidiana de dichas prácticas, lo que nos conduce a repensar desde el papel de las mediciones de audiencias y estadísticas más tradicionales hasta el uso del big data y algoritmos, en tanto diferentes lecturas político-culturales de audiencias hoy desafiadas por una crisis mundial en materia de ciberseguridad. Entre otras condiciones del devenir digital, entenderemos tales consumos contemporáneos como un problema de poder político, reconociendo su dimensión ideológica.
#Digital Culture: Reflections on Contemporary Political Consumption
Keywords: Narrativas; Subjetividad; Performance; Cárceles; Artes escénicas; Comunicación; https://purl.org/pe-repo/ocde/ford#5.09.01